Flow caching effectiveness in packet forwarding applications - Czekaj, Maciej Jakub; Jamro, Ernest (Computer Science, 2019)
Routing algorithms are known to be a potential bottleneck for packet processing. Network flow caching can function as a genneral acceleration technique for packet processing workloads. The goal of this article is to evaluate the effectiveness of packet flow caching techniques in high-speed networks. The area of focus is data distribution characteristics that lead to effectiveness of caching of network flows (connections). Based on statistical analysis and simulations the article sets necessary conditions for effective use of caches in packet forwarding applications. Public domain network traces were examined and measured for data locality. Software simulations show a strong correlation between flow packet distance metric and cache hit rate.